Tumor gene expression signatures associated with outcome in large B−cell lymphoma treated with CD19-directed CAR T−cell therapy (axicabtagene ciloleucel) - Tian, Yuan; Budka, Justin; Locke, Frederick L.; Westin, Jason R.; To, Christina; Tiwari, Gayatri; Mao, Daqin; Bedognetti, Davide; Shen, Rhine R.; Andrade, Jorge; Filosto, Simone (Frontiers in Oncology, 2025)
IntroductionCAR T cell therapy provided transformative outcomes for patients with B-cell lymphoma; however, a large fraction of patients remains at risk for relapse, underlying the need to uncover mechanisms of resistance and predictive biomarkers. Herein, we leveraged the ZUMA-7 phase III randomized trial of relapsed/refractory large B-cell lymphoma (LBCL) patients treated with axicabtagene ciloleucel (axi-cel; CD19-targeting CAR T cells) to discover tumor gene expression signatures (GES) associated with outcome.MethodsWith tumor transcriptomics from 134 axi-cel patients, we employed multivariate penalized Cox models analyzing event-free survival (EFS), progression-free survival (PFS), and duration of response (DOR).Results and DiscussionWe identified two novel GES, a six-gene/transcript signature (6-GES; CD19, CD45RA, CCL22, KLRK1, SOX11, SIGLEC5) correlated with improved outcome after axi-cel (HR: 0.27, 95% CI: 0.16–0.44 for EFS), representing lymphomas with abundant target antigen (CD19) expression, adhesion molecules, and relatively low immune infiltration mostly composed of cytotoxic lymphocytes (T and NK cells) and DCs, and secondly, a 17-gene/transcript signature (17-GES; CD45RO, BCL2, IL-18R1, TNFSF4 [OX40L], KLRB1 [CD161], KIR3DL2, ITGB8, DUSP5, GPC4, PSMB5, RPS6KB1, SERPINA9, NBN,GLUD1, ESR1, ARID1A, and SLC16A1) correlated with disease progression after axi-cel (HR: 6.12, 95% CI: 3.57–10.50 for EFS), consistent with high immune inflammation and escape mechanisms, such as the upregulation of genes involved in repair of damaged DNA or chromatin remodeling, inhibition of apoptosis, and a metabolically restrictive environment. These signatures did not correlate with outcome in the standard-of-care arm of ZUMA-7 (chemotherapy, followed by transplant) or frontline therapy, supporting their predictive rather than prognostic value. The findings were technically reproduced in a subset of ZUMA-7 samples profiled by RNA-seq (axi-cel, n=124; SOC, n=125). The 6-GES was reduced, whereas the 17-GES was elevated at progression post axi-cel, consistent with the notion that these signatures represent features relevant for response and resistance to CAR T-cell therapy.ConclusionOur transcriptomic analysis identified gene expression signatures potentially predictive of outcome with CD19-directed CAR T-cell therapy, and these findings are informative for risk stratification and development of next-generation products.